QT interval prolongation related to afatinib treatment in a patient with metastatic non-small-cell lung cancer - KOCAKAYA, DERYA; DANE, FAYSAL; DEMİRCAN, NAZIM CAN; YUMUK, PERRAN FULDEN; ARIKAN, RUKİYE; BAŞOĞLU TÜYLÜ, TUĞBA; AKIN TELLİ, TUĞBA (MOSBY-ELSEVIER, 2020)
Afatinib improves survival in metastatic non-small-cell lung cancer driven by activating epidermal growth factor receptor mutations. QT interval prolongation is a possible side effect of tar geted anticancer drugs, but this has not been reported before with afatinib. We report a case of metastatic pulmonary adenocarcinoma with epidermal growth factor receptor exon 19 deletion who was treated with first-line afatinib. The patient was started on afatinib with a total dose of 40 mg/day and experienced grade 3 (> 500 ms) QT interval prolongation in the seventh week. Dose was interrupted and then reduced to 30 mg/day after the event repeated. QT prolongation occurred only once with the reduced dose and radiologic oligoprogression was detected. Local therapy was performed and afatinib was continued as 30 mg/day. To the best of our knowledge, this case marks the first QT interval prolongation associated with afatinib. It is prudent to perform a baseline cardiologic evaluation and electrocardiogram monitoring in non-small cell lung cancer patients treated with this drug. (c) 2020 Elsevier Inc. All rights reserved.
Keywords: Afatinib; Epidermal growth factor receptor; Non-small-cell lung cancer; QT prolongation; Tyrosine kinase inhibitor; OPEN-LABEL; CARDIOTOXICITY; ADENOCARCINOMA; CHEMOTHERAPY